Understanding as a Way of Attitude According to Rudolf Bultmann and Demythologizing - Angel Keristina; Arisna Ariyani; Diren Nisapingka; Jeck Thomas Alvin; Jinny Ningsih; Krisina Natalia; Lola Monica; Militon Wandik; Nasa Garuda; Sipora Yuliana Sayori; Sri Apridianti (PT FORMOSA CENDEKIA GLOBAL, 2023)
The existence of the development of Hermeneutics was widely applied by 20th century theologians to apply their thoughts, especially in responding to the existence of myths in the Bible gospels. This shows that it is difficult for post-modern humans to accept the myths contained in the Bible gospels at that time because they are supernatural and irrational. The purpose of this writing is to describe the development of Demythologised Hermeneutics and the resulting influence at this time on Christian values. This study uses a qualitative descriptive method, the data used through literature review with an approach that is in accordance with Rudolf Bultmann's thoughts. Based on the results of Rudolf Bultmann's Demythologizing research centered on the existence of myths, kerygma, as well as historical Jesus and Christ the Faith, and the resulting influences tend to be negative